Pattern of Cutaneous Dermatoses in Type 2 Diabetes Mellitus in a Tertiary Hospital: A Cross Sectional Study - Akhter, Mahfuza; Bhuiyan, Ishrat; Akter, Zubaida; Hossain, Homayra Tahseen; Mowla, Syed Ghulam Mogni (TAJ: Journal of Teachers Association, 2019)
Background: Diabetes mellitus (DM) continues to be a major public health problem. Multiple factors have a role in the skin manifestations of DM. Cutaneous manifestations of DM are very important to the clinician. Methods: Current study was carried out in the Department of Dermatology and Venereology, Shaheed Suhrawrdy Medical College Hospital, Dhaka, spanning from 1st January 2017 till 30th June 2017 over a period of six months. Adult patients already diagnosed to be suffering from type 2 DM presenting with cutaneous manifestations were included in the study. Results: Majority (68.0%) patients had diabetes >5 years, 16.7% had < 1 year and 15.3% had 1-5 years. Family history of DM was found in 70.7% in this study. In this study bacterial infection and fungal infection were more common in female patients (60.0% vs 62.0% respectively). Regarding types of dermatoses, fungal infection was more common in this study 50(33.3%). Others were bacterial infection 20(13.3%), viral infection 7(4.7%) and parasitic infection 7(4.7%). Papulo squamous disease was found 31(20.7%) patients, other diseases were 32(21.3%).Viral infection was more in male patients (71.4%). Parasitic infection was high in female patients 6(85.7%). Papulo squamous diseases was found 21(67.7%) in female patients. Conclusion: In this study fungal infection, bacterial infection, viral infection and parasitic infections were found to be the more common cutaneous dermatoses among adult diabetic patients. Bacterial infection and fungal infection were more common in female patients. TAJ 2018; 31(1): 21-28